Aprepitant for prevention of nausea and vomiting secondary to high-dose Cyclophosphamide administered to patients undergoing Autologous Peripheral Blood Stem Cells mobilization: A Phase II Trial - Abidi, Muneer H (2011)
This is a phase II trial evaluating efficacy and safety of Aprepitant (AP) in combination with 5-HT3 antagonist and adjusted dose dexamethasone in patients receiving high-dose cyclophosphamide (CY) and filgrastim for stem cell mobilization. We used Simon’s optimal two-stage design constrained to fewer than 40 patients with 10% type I error and 85% statistical power. The first stage of the study required accrual of 18 response-evaluable patients. The primary endpoint was the control of vomiting without the use of any rescue anti-emetics at 24 hours after the administration of high dose CY (4gm/m(2)). If emesis was controlled in ≥ 9 patients, an additional cohort of 17 patients would be enrolled. The null hypothesis would be rejected if there were ≥ 20 responses among 35 patients. Forty patients were enrolled, five of whom were not evaluable for response. Eighteen evaluable patients were enrolled in the first stage. Acute emesis was controlled in 10 patients; therefore, enrollment proceeded to stage 2. An additional 17 patients were enrolled; 20/35 response-evaluable patients (57%) did not develop acute vomiting or require rescue anti-emetics, thus achieving the goal of the study. A total of 22/35 response-evaluable patients (63%) met the secondary endpoint of delayed emesis control (days 2–5). Thirty three out of 35 patients underwent successful stem cell mobilization. No ≥ grade 3 AP-related adverse events were noted. The AP regimen can effectively control acute and delayed emesis in the majority patients receiving high-dose CY.